MORTALITY ESTIMATES OF INDIAN RIBBON FISH TRICHIURUS LEPTURUS OFF MAHARASHTRA COAST - MOHITE, ASHISH; BIRADAR, R. S. (Journal of Indian Fisheries Association, 2016)
In view of its new found status in export market, ribbon fish resourcesneed to be continusly monitored. Mortality, one of the important parameteris reported for the Indian ribbon fish Trichiurus lepturus Linnaeus in thepresent communication. The average annual instantaneous rate of total (Z),natural (M) and fishing mortality coefficient (F) were estimated as 2.66, 0. 77and 1.89 respectively for the 1995 to 1997 period. The exploitation rate (U) andexploitation ratio (E) were estimated as 0.66 and 0.71 respectively, which isbeyond the optimum Thursreduction in the fishing effort for this stock alongthe Maharashtra coast is necessary.Keywords : Mortality, Exploitation rate, Trichiurus lepturus.